Respect the weeds digital transformation rooted in principled leadership vision and innovation - Pope, Adan K.; Buonfiglio, Peter J. (Gold River, CA Authority Publishing, 2021)
A true game-changing book, filled with proven tools to inspire you and provide a clear path to a better future for your organization.

Respect the Weeds offers a holistic, yet pragmatic roadmap for digital transformation, designed to provide you with the insights you need to get out of your comfort zone and make the hard decisions required to drive your business model forward.

In this book you will find:
A new perspective on undaunted leadership principles, from conveying humility and authenticity, to building trust, creativity, and positivity
A navigation tool for applying these principles toward a desired outcome, including how to mitigate organizational doubt with strong vision setting
A step-by-step guide to creating a unique industry point of view that drives portfolio innovation and desired outcomes

Thoughtful leaders like you seek to continually challenge themselves to dig deep and find the conviction to set and stick to a plan...to respect your inner weed that will always find a way to thrive even in the most hostile environment.

Many successful organizations are now struggling to apply game-changing technologies that would enable new models and customer experiences before innovators disrupt their core business. Leaders in these organizations that have sought guidance in books on digital roadmaps or organizational theory or self-actualization, in practicality need to integrate all three disciplines, the authors contend.

Adan and Peter's experience in information technology strategy have taught them that leaders need to be open-minded as they weave together thought leadership, innovation, and market-driven perspectives into a real-world digital transformation approach--one that will help them carry their businesses through the uncertainties of Industry 4.0 or Web 3.0 or wherever their digitally-savvy consumers take them.

Respect the Weeds begins by making the case for a new perspective on undaunted leadership principles, from conveying vision and authenticity, to building trust and creativity and a positivity that can be equally applied to the millennial workforce that grew up in the Cloud, the hardened engineers that measure their world by lines of software code, or fellow leaders whose management default is resource competition and outsourcing strategy to dogma-driven consultants.

The authors then demonstrate how these agile leadership principles can be applied--at how deep thinking can mitigate organizational doubt--with strong vision setting, well-researched industry points of view, and stake-in-the-ground portfolio innovation and execution. The digital transformation game is filled with imprecision, moving targets, competing interests, security threats, and the inevitable, sometimes inexplicable, setbacks and failures that must be mitigated with informed judgments about the business, technology and people.

Putting these principles to work is the ultimate goal of this book. More than preaching theory, Adan and Peter hope to impart the courage to try these principles iny our organization, by describing case studies where they have been successfully applied, and by developing potential use cases where a more agile leadership approach will be required for success.

Lastly, the authors know that good leaders need to challenge themselves personally: to dig deep and find the conviction to set and stick to a plan; to know when to challenge the ways of working, resolve conflicts, and when to just let it go. When to close the laptop and pick up the dry erase marker. To fear not the scale and complexity of what lays before them. To compete. To respect your inner "weed" that will always find a way to survive.
Contents: Preface -- Part I. Digital transformation as a game changer and a test of leadership -- Part II. Creating a unique point of view as a foundation for change -- Part III. Putting the plan into action.
Keywords: Transformational leadership; Technological innovations -- Management